2018
DOI: 10.1177/1524838018801327
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Latinx Acculturation and Intimate Partner Violence

Abstract: Objective: Intimate partner violence (IPV) is a serious public health concern that affects many Latinx couples. The present study conducted a systematic review and meta-analysis to quantitatively assess acculturation as a predictor of IPV among Latinxs and subgroup analyses to evaluate the effect size by gender and type of acculturation measure. Method: The meta-analysis implemented the preferred reporting items for systematic reviews and meta-analyses guidelines to retrieve studies assessing the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…[5,7] It is possible that these gender inequalities, and therefore IPV, are reduced among young immigrants due to the influence of the host country. These gender inequalities could be maintained in the adult immigrant population due to a lower cultural permeability of the adult population in the host society [30] It is also possible that immigrant women have more difficulties escaping situations of violence than native-born women, as shown in prior studies. [10]…”
Section: Discussionmentioning
confidence: 99%
“…[5,7] It is possible that these gender inequalities, and therefore IPV, are reduced among young immigrants due to the influence of the host country. These gender inequalities could be maintained in the adult immigrant population due to a lower cultural permeability of the adult population in the host society [30] It is also possible that immigrant women have more difficulties escaping situations of violence than native-born women, as shown in prior studies. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of expected relations in this study (e.g., IPV with parenting and toddler behavior) suggest that the manifestation and outcomes of IPV may be distinct in this population. For example, characteristics of the immigrant Latinx cultural context may affect IPV's impact on families, such as the protective factor of familismo or the risk factor of machismo (Alvarez et al, 2020;Klevens et al, 2007;Sabina et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have called for research on the processes related to IPV among Latinx families, including the role of immigration (Alvarez & Fedock, 2018;Gonzalez et al, 2020). The literature points to several cultural factors related to Latinx immigrant women's experience of IPV, such as acculturation, language barriers, and immigration status (Alvarez et al, 2020;González-Guarda et al, 2009;Raj & Silverman, 2002). The limited literature on IPV's effects on Latinx women suggests high rates of depression and PTSD (Rodriguez et al, 2008), but is notably sparse with respect to parenting processes.…”
mentioning
confidence: 99%
“…Two indicators frequently used as proxies of acculturation when an acculturation scale is not available are nativity and language preference (Alvarez et al, 2018). Researchers studying Hispanic samples have found that these measures are associated with adoption of host cultural practices, an index of acculturation (Schwartz, Pantin, Sullivan, Prado, & Szapocznik, 2006).…”
Section: Acculturation In Hispanic Familiesmentioning
confidence: 99%